Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/dc.23160
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology of non‐small cell lung carcinoma with anaplastic lymphoma kinase gene rearrangement

Abstract: Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase demonstrating activating mutations in several malignancies including a subset (1-5%) of non-small cell lung carcinomas (NSCLC). Prior work examining, the histologic features of these tumors found a spectrum of findings, notably a solid/acinar pattern, as well as a mucinous cribriform pattern. We present the first study to date describing the cytomorphology of NSCLC harboring ALK rearrangements. A retrospective database search was conducted to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 17 publications
(35 reference statements)
1
33
0
Order By: Relevance
“…This observation was consistent with another study, which showed that ALK-positive adenocarcinomas might metastasize to lymph nodes early, despite the small size of the primary tumor (Jokoji et al, 2010;Paik et al, 2012;Takamochi et al, 2013). To date, several small sample studies (Takahashi et al, 2010;Zhang et al, 2014;Toll and Maleki, 2015) have reported that ALK rearrangements were associated with moderate or poor differentiation status; our study further affirmed this finding in a relatively larger sample size.…”
Section: Discussionsupporting
confidence: 93%
“…This observation was consistent with another study, which showed that ALK-positive adenocarcinomas might metastasize to lymph nodes early, despite the small size of the primary tumor (Jokoji et al, 2010;Paik et al, 2012;Takamochi et al, 2013). To date, several small sample studies (Takahashi et al, 2010;Zhang et al, 2014;Toll and Maleki, 2015) have reported that ALK rearrangements were associated with moderate or poor differentiation status; our study further affirmed this finding in a relatively larger sample size.…”
Section: Discussionsupporting
confidence: 93%
“…8,14,15 Ha et al reported that ALK-positive cancer was characterized by an individually scattered pattern of SRCC. 8,14,15 Ha et al reported that ALK-positive cancer was characterized by an individually scattered pattern of SRCC.…”
Section: Appearance Patterns Of Srccmentioning
confidence: 99%
“…4 EGFR-positive tumors are reportedly associated with lepidic growth (visible as a flat or monolayer architecture on cytology) in histological specimens and with the presence of intranuclear inclusions in cytological specimens. [6][7][8][9] Previous histological studies have shown that solid signet ring cell carcinoma (SRCC) and a mucinous cribriform structure are observed in ALK-positive cancers. [6][7][8][9] Previous histological studies have shown that solid signet ring cell carcinoma (SRCC) and a mucinous cribriform structure are observed in ALK-positive cancers.…”
mentioning
confidence: 99%
See 2 more Smart Citations